Produção de massa seca e nutrição de cultivares de arroz de terras altas sob condição de déficit hídrico e adubação silicatada - Mauad, Munir; Costa Crusciol, Carlos Alexandre [UNESP]; Grassi Filho, Hélio [UNESP] (Universidade Estadual de Londrina (UEL), 2011)
Although silicon has not been considered an essential element for plant growth and development, it has provided several benefits for the rice crop, especially under biotic and abiotic stress. The objective of this work was to evaluate macronutrient and silicon levels in upland rice cultivars cropped under water deficit and silicon fertilization. The experiment was carried out in greenhouse and the design was the completely randomized block, analyzed as a 2 x 2 x 2 factorial, which consisted of two cultivars, 'Maravilha' (modern group) and 'Caiapo' (traditional group), two silicon rates (0 and 350 kg ha(-1)) and two soil water tensions (-0.025 MPa and -0.050 MPa). Plant dry matter of the 'Maravilha' cultivar was higher compared to the other material. Higher soil water tensions decreased plant dry matter and macronutrient levels. Upland rice cultivars respond distinctively to soil water tensions and silicon rates.
Dry matter and plant nutrition of upland rice under water deficit and silicon fertilization
Keywords: Oryza sativa L.; silicon; macronutrients; water soil tension